The scalping of the great Sioux nation : a review of my life on the Rosebud and Pine Ridge reservations - Davis, Philip E. (Hamilton Books, 2010)
The Scalping of the Great Sioux Nation recalls Davis' early upbringing and education on two Indian reservations. Davis also assesses the policies of the United States government regarding the status of Indians in society. Scalping is not too stronga term to describe the multiple injustices which the Sioux tribes of South Dakota and elsewhere have suffered. The general hate and bigotry which Custer often displayed toward Indians (and blacks) only reflected a similar feeling among many white settlers, presidents, and congressmen. The Indian struggle for survival, self-governance, and sovereignty.